Angiosarcoma: clinical and imaging features from head to toe - Gaballah, Ayman H; Jensen, Corey T; Palmquist, Sarah; Pickhardt, Perry J; Duran, Alper; Broering, Gregory; Elsayes, Khaled M (British journal of radiology, 2017)
Angiosarcoma is a rare, aggressive subtype of soft-tissue sarcoma with a propensity for local recurrence and metastasis associated with a generally poor prognosis, unless diagnosed early. Given the vascular endothelial cell origin of angiosarcoma, tumours may develop in essentially any organ; however, there is a predilection for the skin where half of all tumours arise, increasing in prevalence with age. The most common risk factors are chronic lymphoedema and history of radiation. We review the most important radiological findings along the spectrum of angiosarcoma from head to toe throughout the body, including uncommon and rare locations. Key imaging features of angiosarcoma across multiple organ systems will be described, as well as the impact on management and prognosis.